Effects of STEAM-Based Chemistry Learning on High School Students’ Critical Thinking Skills: A Systematic Review - Dasi, Ni Made Ayu Hari Laksmi Dewi; Dasi, Krisna Jiwani Dewi; Redhana, I Wayan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
In the 21st century, the world of education faces new challenges that are far more comprehensive and multidimensional. Education in this century requires students to adapt to developments in science by mastering 21st-century competencies, including critical thinking. Chemistry learning as part of the science field is one of the educational facilitators that has great potential in developing critical thinking skills. However, in reality, chemistry is often considered a difficult subject because it involves complex, invisible (submicroscopic) concepts that require high analytical skills. One relevant approach to improving critical thinking skills is the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach. The purpose of this study was to analyse the effect of the STEAM approach on high school students’ critical thinking skills in chemistry. This study used the Systematic Literature Review (SLR) method, which analyses relevant articles using inclusion and exclusion criteria in accordance with the PRISMA guidelines. The exclusion criteria include articles that are not fully accessible, non-empirical articles (e.g., opinions, editorials), articles that measure contexts other than high school/MA chemistry, and articles that do not measure critical thinking skills. On the other hand, the inclusion criteria in this SLR included articles published between 2015 and 2025, research contexts on high school/MA students, a focus on the application of STEAM in chemistry learning, peer-reviewed articles (journals, proceedings, published theses), and articles that measured critical thinking skills. The study found that the STEAM approach in chemistry instruction was effective in improving high school students’ critical thinking skills.